Cover Picture: Durable Nickel‐Iron (Oxy)hydroxide Oxygen Evolution Electrocatalysts through Surface Functionalization with Tetraphenylporphyrin (Angew. Chem. Int. Ed. 51/2022). Issue 51 (2nd December 2022) - Kang, Sinwoo; Im, Changbin; Spanos, Ioannis; Ham, Kahyun; Lim, Ahyoun; Jacob, Timo; Schlögl, Robert; Lee, Jaeyoung
Abstract : State‐of‐the‐art nickel–iron oxyhydroxide catalysts suffer from loss of iron under oxygen evolution reaction (OER) potential. In their Research Article (e202214541 ), Jaeyoung Lee and co‐workers develop a stable OER electrocatalyst by adding tetraphenylporphyrin protective layers. They accelerate the redeposition of eluted iron onto the electrocatalyst by forming a nonpolar–polar interface. This not only prolongs the iron population but also the lifetime of the electrocatalyst.